Energy-Resolving X-ray Imaging at 1 MHz Frame Rate – The HEXITECMHZ ASIC. Issue 1 (1st December 2022) - Jones, L. L.; Bell, S.; Church, I.; Cline, B.; Gardiner, T.; Hart, M.; Holden, J.; Nicholls, T.; Nobes, J.; Prydderch, M.; Roberts, M.; Seller, P.; et al.
Abstract: HEXITECMHZ is an ASIC developed to deliver spectroscopic x-ray imaging at frame rates up to 1MHz for future high-flux-rate applications. Optimised for sensing electron signals from detector materials such as CdTe, CZT, GaAs, and p-type silicon detectors, the design has an array of 80×80 pixels on a pitch of 250 μm, with each pixel capable of measuring single x-ray photons up to energies of 200 keV, with a resolution of 1 keV FWHM. Further improvements in the spatial and spectroscopic resolution are possible due to the pixel's ability to simultaneously sense positive signals up to 20 keV induced by internal weighting-potential effects from electron signals on neighbouring pixels. A count rate limit of around 10 6 photons s -1 mm -2 is achieved by converting the signals from all pixels every 1 μs using 12-bit time-to-digital converters – an improvement of two orders of magnitude over previous HEXITEC ASICs. To save power, each converter is shared between groups of eight pixels. Each 76.8kbit data frame is Aurora 64b/66b encoded and serialised over twenty lanes of differential CML, all operating in parallel at 4.1 Gbit/s. In this paper, we present details of the design, including preliminary test results from the ASIC.